Act of February 14, 1887, § 3, ALBANY, CHARTER AND GENERAL ORDINANCES (C. W. Watts 1887). - (:unkn) unknown (General Publisher, 1887)
regulated the storage of gunpowder, discharge of firearms, and carrying of concealed firearms
--
Keywords: GUN POWDER STORAGE; DISCHARGE; CARRY - CONCEALED